Factors related to menstrual cycle irregularity in adolescent females - Nofriza Rahmayani; Herwansyah Herwansyah; Marta Butar Butar; Sri Astuti Siregar; Usi Lanita (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Adolescence is an important transitional phase marked by physiological and psychological changes, including the onset of menstruation. Menstrual cycle irregularities in adolescents are a common reproductive health problem, and are influenced by various factors such as physical activity, stress levels, sleep quality, and body mass index (BMI). Purpose: This study aims to analyze factors associated with menstrual cycle irregularities in female adolescents. Method: This study uses an analytical quantitative design with a cross-sectional approach. The study population was all female students of SMA Negeri 4 Jambi City. A total of 87 respondents were selected using a stratified random sampling technique. Data were collected using the International Physical Activity Questionnaire (IPAQ), Perceived Stress Scale-10 (PSS-10), Pittsburgh Sleep Quality Index (PSQI), and menstrual cycle observation sheets. Data analysis was performed univariately and bivariately using the Chi-Square test (α = 0.05). Result: The study showed a significant association between physical activity (p=0.035), stress levels (p=0.038), sleep quality (p=0.049), and BMI (p=0.028) and menstrual cycle irregularity. Conclusion: The conclusion of this study is that Physical activity, stress, sleep quality, and BMI were significantly associated with menstrual cycle irregularity. Promotive-preventive interventions through reproductive health education and strengthening the PIK-R or GENRE program in schools are needed to increase awareness and healthy lifestyle behaviors among adolescents.